Efficient and stable perovskite solar cells prepared in ambient air irrespective of the humidity - Qidong Tai (Nature Portfolio, 2016)
Poor stability of perovskite solar cells in humid conditions has hindered device fabrication and operation. Here, Tai et al. report the use of a lead thiocyanate precursor in preparing perovskite solar cells and without encapsulation showed better stability in air than typical perovskite solar cells.